2017
DOI: 10.1080/00224499.2017.1366411
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sex-Related Alcohol Expectancies in Alcohol-Involved Consensual and Nonconsensual Sex Among Women of Asian/Pacific Islander and Women of European Race/Ethnicity

Abstract: Alcohol-involved sexual experiences, including incapacitated sexual assault and alcohol-involved sex, are major public health concerns among college women. Further, racial/ethnic diversity among college students is increasing, particularly with regard to increases in college students of Asian/Pacific Islander race/ethnicity. Of relevance, evidence suggests differences in sexual assault rates across ethnicities and cultures; however, no known study to date has examined differences by ethnicity and first languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Among a sample of Thai and Vietnamese women who work in massage parlors ( n = 43), lack of legal documentation and sex work history was associated with non-partner sexual violence (Nemoto et al, 2004). Dir et al (2018) used native language as a proxy for acculturation and found that non-native English speakers experienced a lower rate of sexual assault in which the victim was physically incapacitated compared to native English speakers (Dir et al, 2018). First generation Japanese immigrants experienced sexual violence (i.e., unwanted touching, sexual assault, stalking, exhibitionism, obscene phone calls, and voyeurism) at a higher prevalence compared to 1.5 (foreign-born but grew up in United States) or higher generation individuals (Yoshihama, 2001a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among a sample of Thai and Vietnamese women who work in massage parlors ( n = 43), lack of legal documentation and sex work history was associated with non-partner sexual violence (Nemoto et al, 2004). Dir et al (2018) used native language as a proxy for acculturation and found that non-native English speakers experienced a lower rate of sexual assault in which the victim was physically incapacitated compared to native English speakers (Dir et al, 2018). First generation Japanese immigrants experienced sexual violence (i.e., unwanted touching, sexual assault, stalking, exhibitionism, obscene phone calls, and voyeurism) at a higher prevalence compared to 1.5 (foreign-born but grew up in United States) or higher generation individuals (Yoshihama, 2001a).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 16 articles discussed various cross-sectional factors (i.e., no temporal relationships were assessed) associated with non-partner sexual violence (N. T. Buchanan et al, 2009; Buchanan et al, 2018; Crisanti et al, 2011; Devries et al, 2011; Dir et al, 2018; Hahm et al, 2012, 2017; Jewkes, Jama-Shai, & Sikweyiya, 2017; Kelly-Hanku et al, 2015; McLaughlin et al, 2019; Nemoto et al, 2004; Nguyen et al, 2010; Nusbaum et al, 2005; Pape et al, 2016; Tummala-Narra et al, 2019; Yoshihama, 2001a). Articles were mostly quantitative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations